Rendering-Oriented Decoding for a Distributed Multiview Coding System Using a Coset Code. (22nd April 2009) - Taguchi, Yuichi; Naemura, Takeshi
Abstract : This paper discusses a system in which multiview images are captured and encoded in a distributed fashion and a viewer synthesizes a novel image from this data. We present an efficient method for such a system that combines decoding and rendering processes in order to directly synthesize the novel image without having to reconstruct all the input images. Our method jointly performs disparity compensation in the decoding process and geometry estimation in the rendering process, because they are essentially equivalent if the camera parameters for the input images are known. Our method keeps both encoder and decoder complexity as low as that of a conventional intracoding method, while attaining better coding performance owing to the interimage decoding. We validate our method by evaluating the coding performance and the processing time for decoding and rendering in experiments.